Dogsong - Paulsen, Gary. (New York : Aladdin Paperbacks, 1995)
A fourteen-year-old Eskimo boy who feels assailed by the modernity of his life takes a 1,400-mile journey by dog sled across ice, tundra, and mountains seeking his own "song" of himself.
Newbery Medal/Honor.
Wilson's Children.
Wilson's Junior High School.
Booklist, August 2004.
Notable/Best Books (A.L.A.), December 2008.
School Library Journal, September 2004.
Keywords: Eskimos -- Fiction; Inuit -- Fiction